Exposed Science : Genes, the Environment, and the Politics of Population Health - SARA SHOSTAK (University of California Press, 2013)
In the spring of 2000, a two-year-old girl named Sunday Abek was treated at a New Hampshire hospital emergency room for a low-grade fever and vomiting. Because her throat culture was positive for strep, the doctors sent her home with a prescription for an antibiotic. Her condition worsened, and three weeks later Sunday was admitted to the hospital, where she fell into a coma. Two days later, she died. The cause of her death was lead poisoning. Originally from Sudan, Sunday’s family had recently moved to the United States from an Egyptian refugee camp, where she had lived for most of her brief life. She was poisoned, however, by lead in her family’s home in an apartment building in Manchester, New Hampshire. Following her death, testing at the apartment revealed that the porch, where Sunday played, was covered with peeling, fl aking paint